Agency of the leaders of the Independent Union of Nurses and Health Technicians: Mobilization for participation in the elections of joint administrative committees - Sofia El Yahyaoui; Abdelhamid BENKHATTAB (Moroccan Journal of Quantitative and Qualitative Research)
Abstract. From the 70s and 80s, several political science works have focused on the way in which actors interact with institutions and how they act through their capacities on the environment. To explain the change institutional, neo-institutional theory (NIT) has integrated this agentic turn thanks to some of his works from the thirty latest years. Our manuscript aimed to explore the capacity action of twelve founders of the Union Independent of Nurses and Health Technicians (SIITS) on their environments, with a view to mobilizing in favor of the constraints linked to its institutionalization, constraining their participation in elections of administrative joint administrative committees (CAP) organized in 2021. Semi- structured interviews carried out between 2023 and 2024 identified an ability action strategic in a neo-corporatist field structure conflictual, marked by the domination of unions inter-categorical opposing the introduction of a category of actor, proclaiming the representation of nursing interests. Faced with this complexity institutional, the founders of SIIITS considered as institutional entrepreneurs used their skills and roles social to establish an institutional DIY the day before the 2021 elections between the first union autonomous nurses, inactive since its creation in 2007 and their unauthorized union after its creation in 2020.